Highlights of the IFPRI and IFAD partnership: Working together to ensure food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The International Fund for Agricultural Development (IFAD) and the International Food Policy Research Institute (IFPRI) were both created in response to the food crises of the 1970s. We have worked together for more than 20 years to catalyze agricultural and rural development and improve food security in Africa, Asia, and Latin America. IFAD and IFPRI have strengthened the productivity and resilience of smallholder farmers and other rural people, with a particular focus on helping expand their access to innovative local farming methods, climate change mitigation and adaptation technologies and financing, and more profitable markets. To further promote rural development and transformation, IFAD and IFPRI have built cutting-edge information systems and tools that deliver sound data and analyses to governments, donors, farmer organizations, and other stakeholders. As a result, the two organizations have fostered evidence-based policy making and investments that promote agricultural growth and rural development.